New nanocomposite material as supercapacitor electrode prepared via restacking of Ni-Mn LDH and MnO2 nanosheets. (1st September 2017) - Quan, Wei; Jiang, Caihua; Wang, Shitong; Li, Yesheng; Zhang, Zhongtai; Tang, Zilong; Favier, Frédéric
Abstract: A new pseudocapacitive nanocomposite is reported in this article. Such amorphous materials were prepared via restacking of Ni-Mn LDH and MnO2 nanosheets obtained by exfoliation treatments. Synergetic effects of the two components were demonstrated in both alkaline and neutral aqueous electrolytes, as rate capability and cycle stability were both greatly improved compared to each-component samples and mixture. Tests on an activated carbon//nano-composite asymmetric device reveal that the energy density could be about 16 Wh/Kg at a power density of 15 KW/Kg in alkaline electrolytes, while in neutral electrolytes, the value reached about 13 Wh/Kg at a power density of 9 KW/Kg, matching with many other composition technologies. Besides, rather small leakage and self-discharge currents further indicate its promising applications in practical areas.